Evaluation of raw and processed full-fat soybeans for high-producing dairy cows - Ward, G.M.; Morrill, J.L.; Morrill, M.B.; Dayton, A.D. (Kansas Agricultural Experiment Station, 2012)
Rations containing either soybean meal, raw full-fat soybeans, or processed soybeans were compared using 36 high-producing dairy cows in early lactation. The processed soybeans were heated in a California Pellet Milt Jet-Sploder for sufficient time (about 1 min) to produce beans with exit temperature of 340°F. The raw soybeans and heated soybeans were rolled before being• mixed into the concentrate mixture. Alfalfa hay and concentrate were consumed ad libitum in a ratio of 35 % hay and 65 % concentrate. Milk production and percent protein in milk were significantly greater when cows were fed soybean meal or Jet-Sploded beans than when fed raw soybeans. Percent milkfat and total milk solids were not affected by treatment.
Keywords: Dairy; Soybeans; Milk production; Protein